Developing tourism products in line with Islamic beliefs: some insights from Nabeul–Hammamet. Issue 1 (1st January 2017) - Carboni, Michele; Perelli, Carlo; Sistu, Giovanni
ABSTRACT: In recent years, the interest of both the tourism industry and the academic world in Muslims as consumers with specific requirements has grown remarkably. Attracting Muslim tourists is considered a good business opportunity in an increasing number of Muslim and non-Muslim countries. Tunisia is one of the most important destinations for international tourism in the Middle East and North Africa. Despite being a Muslim-majority country, no significant effort has been made as yet to reach the growing demand for tourism products in line with Islamic beliefs. This study investigates the opinions of a group of 19 key informants in Nabeul–Hammamet concerning the possibility of developing such products. This research shows that tourism operators are becoming progressively more familiar with the global opening up to products designed for Muslim consumers. Opportunities offered by this segment have been recognised, and clear signs are emerging of a proactive attitude towards Muslim-oriented tourism as a differentiation tool.